(untitled) (Журнал «Маркетинг», 2024)
Purpose: This article aims to explore and compare digital marketing trends in Uzbekistan and Indonesia for 2024. It highlights the significance of digital marketing in these emerging markets, identifying key drivers, challenges, and opportunities. Methods: The research utilizes a comprehensive literature review, analyzing academic papers, industry reports, and case studies from both regions. Data was collected through secondary sources and analyzed using qualitative methods to identify prevalent trends and future projections. Findings: The study finds that both Uzbekistan and Indonesia are experiencing rapid digital transformation, driven by technological innovation and increasing internet penetration. In Uzbekistan, digital marketing trends are characterized by the adoption of innovative technologies and a growing emphasis on sustainable practices. In Indonesia, the digital economy is expanding rapidly, with significant growth in ecommerce and digital payments, particularly among MSMEs. The study highlights the need for businesses to adapt to these trends to remain competitive and for policymakers to support digital infrastructure and education.